PELATIHAN EKOWISATA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN BAGI PEMANDU WISATA LOKAL DI DESA PELAGA KECAMATAN PETANG KABUPATEN BADUNG - I Made Bayu Wisnawa (Universitas Triatma Mulya, 2022)
Community service activities with the theme of ecotourism natural tour guide training aim to prepare for implementing ecotourism in the new normal era. The focus of activities is to increase ecotourism knowledge. The method used is lecture and discussion. The training materials provided include the basics of tourism, the history of Bali tourism, ecotourism, CHSE, principles of ecotourism implementation, and the SAVE market segment (Science, Academic, Volunteer, Education). Success is measured by a paired t-test. The instruments used were pre- test and post-test questionnaires. The results of the activity showed an increase in participants' knowledge of 7.5 points, with a paired sample t-test significance of 0.0001.